Leaders in Social Movements: Evidence from Unions in Myanmar - Boudreau, Laura; Macchiavello, Rocco; Minni, Virginia; Tanaka, Mari (American Economic Review, 2025)
Social movements are catalysts for crucial institutional changes. To succeed, they must coordinate members’ views (consensus building) and actions (mobilization). We study union leaders within Myanmar’s burgeoning labor movement. Union leaders are positively selected on both ability and personality traits that enable them to influence others, yet they earn lower wages. In group discussions about workers’ views on an upcoming national minimum wage negotiation, randomly embedded leaders build consensus around the union’s preferred policy. In an experiment that mimics individual decision-making in a collective action setup, leaders increase mobilization through coordination. (JEL D91, J38, J51, O15)